Effect of initial oil concentration and dispersant on crude oil biodegradation in contaminated seawater - Zahed, M.A. (2010)
The effects of initial oil concentration and the Corexit 9500 dispersant on the rate of bioremediation of petroleum hydrocarbons were investigated with a series of ex-situ seawater samples. With initial oil concentrations of 100, 500, 1,000 and 2,000 mg/L, removal of total petroleum hydrocarbons (TPHs) with dispersant were 67.3%, 62.5%, 56.5% and 44.7%, respectively, and were 64.2%, 55.7%, 48.8% and 37.6% without dispersant. The results clearly indicate that the presence of dispersant enhanced crude oil biodegradation. Lower concentrations of crude oil demonstrated more efficient hydrocarbon removal. Based on these findings, bioremediation is not recommended for crude oil concentrations of 2,000 mg/L or higher.